Herpesviral ICP0 Protein Promotes Two Waves of Heterochromatin Removal on an Early Viral Promoter during Lytic Infection - Jennifer S. Lee (American Society for Microbiology, 2016)
ABSTRACT Herpesviruses must contend with host cell epigenetic silencing responses acting on their genomes upon entry into the host cell nucleus. In this study, we confirmed that unchromatinized herpes simplex virus 1 (HSV-1) genomes enter primary human foreskin fibroblasts and are rapidly subjected to assembly of nucleosomes and association with repressive heterochromatin modifications such as histone 3 (H3) lysine 9-trimethylation (H3K9me3) and lysine 27-trimethylation (H3K27me3) during the first 1 to 2 h postinfection. Kinetic analysis of the modulation of nucleosomes and heterochromatin modifications over the course of lytic infection demonstrates a progressive removal that coincided with initiation of viral gene expression. We obtained evidence for three phases of heterochromatin removal from an early gene promoter: an initial removal of histones and heterochromatin not dependent on ICP0, a second ICP0-dependent round of removal of H3K9me3 that is independent of viral DNA synthesis, and a third phase of H3K27me3 removal that is dependent on ICP0 and viral DNA synthesis. The presence of ICP0 in transfected cells is also sufficient to promote removal of histones and H3K9me3 modifications of cotransfected genes. Overall, these results show that ICP0 promotes histone removal, a reduction of H3K9me3 modifications, and a later indirect reduction of H3K27me3 modifications following viral early gene expression and DNA synthesis. Therefore, HSV ICP0 promotes the reversal of host epigenetic silencing mechanisms by several mechanisms. IMPORTANCE The human pathogen herpes simplex virus (HSV) has evolved multiple strategies to counteract host-mediated epigenetic silencing during productive infection. However, the mechanisms by which viral and cellular effectors contribute to these processes are not well defined. The results from this study demonstrate that HSV counteracts host epigenetic repression in a dynamic stepwise process to remove histone 3 (H3) and subsequently target specific heterochromatin modifications in two distinct waves. This provides the first evidence of a stepwise reversal of host epigenetic silencing by viral proteins. This work also suggests that targets capable of disrupting the kinetics of epigenetic regulation could serve as potential antiviral therapeutic agents.